Multilevel Code Cleaning using Root Extract Method for Java Programs - Kapila, Pooja; Sharma, A; Kaur, N (International Journal of Computer Sciences and Engineering, 2018)
The code cleaning requires the incorporation of the various processes to remove the clones from the source code as well as the programming irregularities, which improve the overall design of the code. In this paper, the proposed model has been designed for the purpose of code cleaning by using the multi-factor code cleaning algorithm. The proposed model is entirely based upon the elimination of the source code irregularities, which contains the bad smells, code clones and other such problems. The proposed model is designed to work in the three primary components, which includes the code clone and smell detection and marking algorithm, which is followed by the refactoring method estimation and then the application of the refactoring application in the final phase for the act of cleaning the source code. The proposed model utilizes the divide and conquer method, which is concerned with the extraction of the methods from the class files. Also the proposed model analyzed and extracts the independent statements from the extracted methods, which incorporates the common statement elimination, which removes the common statements from the duplication removal process. The proposed model has been designed to refactor the code on the basis of the bad smell detection and elimination with the appropriate method. The proposed model has been analyzed under the various kinds of the datasets for the experimental evaluation, where it has been found better. The proposed model has been recorded with the significant values of the parameters of the accuracy, precision and recall.